An in-depth analysis of research on posthepatectomy liver failure (2006-2024): exploring trends and future directions through a bibliometric approach - Wu, Yachen; Li, Jiangtao; Liu, Zhaohai; Jiang, Mengliang; Liang, Hao; Ameer, Sajid; Qu, Xilin; Long, Zhangtao; Zhu, Zhu; Dai, Xiaoming (Frontiers in Medicine, 2025)
ObjectiveThis study aims to identify global hotspots and future trends within the research on posthepatectomy liver failure (PHLF).DesignBibliometric analysis through science mapping and performance analysis.Data sourcesThe Web of Science Core Collection.Data extraction and synthesisThe Web of Science Core Collection database was searched for literature related to PHLF from 2006 to 2024. The authors, publishing institutions, countries, cited literature, journals, and keywords of the included studies were utilized for bibliometric analysis using CiteSpace and VOSviewer.ResultsThe analysis included 986 publications authored by 296 researchers from 60 countries and 246 institutions across 292 journals. The most prolific authors were Aldrighetti Luca, Cescon Matteo and Sparrelid Ernesto. The institutions with the most publications were Naval Medical University, Ruprecht Karls University Heidelberg, and the University of Amsterdam. The countries with the largest number of publications were China, Japan, and the United States. The most commonly cited literature was “posthepatectomy liver failure: a definition and grading” by the International Study Group of Liver Surgery (ISGLS). Annals of Surgery ranked first in the number of co-citations among journals. Currently, the research hotspots of PHLF focus primarily on novel surgical procedures such as liver venous deprivation, associating liver partition and portal vein ligation for staged hepatectomy, and the prediction of PHLF.ConclusionOur study elucidates the global research status of PHLF and clarifies the relevant research hotspots and trends, providing clinicians and researchers with a better understanding of the state of the art and directions for future research.